Exploring Universal Grammar in Arabic Communicative Learning: A Study in Arabic Education Programs - Failasuf, Chakam; Sarip, Mohammad; Khambali, Khambali; Nurhasanah, Nurhasanah (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2024)
Universal Grammar (UG) gives an idea that the world's language formula is the same. Therefore, the Arabic grammar system (L2), which is considered complex, can be simplified with the simple logic of the first language (L1). Grammar logic L2 to L1 can be implemented in Communicative Language Teaching (CLT), which is synthesised from simple grammar and language themes to complex materials. This research uses a descriptive qualitative approach that shows the preparation of teaching materials that combine UG and CLT. The data sources collected are scientific articles, library studies and lecture documents. The results of the research show that the communicative themes used for language practice can be structured in a series parallel to the UG material i.e. from simple SVO where the subject differs from the gender side to a complex SVO in which 1) subjects differ from the gender, numbers and pronouns, 2) verbs differ from the time, 3) objects differ from the gender, the number and pronouns.